2013
DOI: 10.1073/pnas.1307158110
|View full text |Cite
|
Sign up to set email alerts
|

Chain conformations dictate multiscale charge transport phenomena in disordered semiconducting polymers

Abstract: Existing models for the electronic properties of conjugated polymers do not capture the spatial arrangement of the disordered macromolecular chains over which charge transport occurs. Here, we present an analytical and computational description in which the morphology of individual polymer chains is dictated by well-known statistical models and the electronic coupling between units is determined using Marcus theory. The multiscale transport of charges in these materials (high mobility at short length scales, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 51 publications
4
158
0
Order By: Relevance
“…Recent work suggests that interchain transport and intrachain transport operate at different time-scales, and that this distinction can be used to qualitatively explain a large body of experimental work. 54 In ref 54, by distinguishing between (slow) interchain and (fast) intrachain transport, the authors were able to explain the multiscale nature of mobility that has been reported in a variety of materials. 55,56 We use this as a motivation to distinguish between interchain and intrachain regions in hole pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work suggests that interchain transport and intrachain transport operate at different time-scales, and that this distinction can be used to qualitatively explain a large body of experimental work. 54 In ref 54, by distinguishing between (slow) interchain and (fast) intrachain transport, the authors were able to explain the multiscale nature of mobility that has been reported in a variety of materials. 55,56 We use this as a motivation to distinguish between interchain and intrachain regions in hole pathways.…”
Section: Resultsmentioning
confidence: 99%
“…So, rather than assuming a density of states (DOS) and an independent constant localization length we generate the oneelectron states involved in the transport by computing the eigenstates of a random electronic Hamiltonian [13]. This is defined for a polymer chain as el 0…”
Section: B Exp a E K T  mentioning
confidence: 99%
“…We will compare with experimental data extrapolated to the same limit, while generalizations, including to non-equilibrium situations, would be possible within the model but are not considered here. We ignore the role of inter-chain hopping, which has been shown to be correct for polymers with very long persistence length [21], with means to extend the results to the general case recently proposed in [13] at the cost of additional parameters in the model. These corrections could become more significant if the inter-chain hopping had substantially different transport characteristics from the intra-chain one.…”
Section: B Exp a E K T  mentioning
confidence: 99%
“…orphology and excitonic coupling are among the most important factors dictating the functions and performance of conjugated polymers (CPs) in a variety of optoelectronic applications (1)(2)(3)(4). To tune and optimize the morphological and optoelectronic properties of CPs, chemical structure modification of the backbone and side chains is one of the main and most effective approaches (5)(6)(7).…”
mentioning
confidence: 99%